LINGUOCULTURAL FEATURES OF COLORS IN ADVERTISING AND MARKETING DISCOURSE (Ustozlar uchun, 2026)
This article examines the linguocultural dimensions of color symbolism in advertising and marketing discourse, investigating how colors function not merely as visual stimuli but as culturally encoded semiotic units that carry distinct connotations across linguistic and cultural communities. The article concludes that effective intercultural marketing discourse requires a thorough understanding of color semantics within their respective linguocultural contexts.